TERMITES ASOCIADAS A ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ ð˜¨ð˜³ð˜¢ð˜¯ð˜¥ð˜ªð˜´ W.HILL Ex MAIDEN EN EL NOROESTE DE LA PROVINCIA DE CORRIENTES (ARGENTINA) - Laffont, Enrique Rafael; Torales, Gladys Josefina; Arbino, Manuel Osvaldo; Godoy, Maria Celina; Porcel, Eduardo Adolfo; Coronel, Juan Manuel (REVISTA DE AGRICULTURA, 2020)
TERMITES ASOCIADAS A ð˜Œð˜¶ð˜¤ð˜¢ð˜ð˜ºð˜±ð˜µð˜¶ð˜´ ð˜¨ð˜³ð˜¢ð˜¯ð˜¥ð˜ªð˜´ W.HILL Ex MAIDEN EN EL NOROESTE DE LA PROVINCIA DE CORRIENTES (ARGENTINA)